A monitoring and control system for EV charging station - Chen, TianQi. (2013)
Electric Vehicles (EVs) are increasingly being considered as a sustainable mode of transport nowadays due to its higher efficiency and no carbon emissions compared to internal combustion engines. Furthermore, concept of Vehicle‐to‐Grid (V2G) is becoming more and more popular with gridable vehicle since most vehicles are parked for almost an average of 95 percent of the time and their batteries could be used to let electricity flow from the car to the grid and back. Therefore, this project is designed to build a monitoring a monitoring and control system for electric vehicle to investigate the impact of EV connection to local distribution networks. The main objective of the project is to build a database to store the charging and discharging process of EV and energy consumption of the process. The method adopted in this project was to use serial communication on the EV charging and discharging simulation system. C# programs and MySQL were applied in this project to read data from serial port, store data to database and export data to excel format from database. Then the data were analyzed for the impact on the distribution networks. To conclude, during the charging process, with large number of electric vehicles connected to the grid, power quality, load characteristics, electrical equipment and so on would be impacted. On the other hand, during the discharging process, wastage of power energy could be avoid and peak modulation and reactive power compensation could be made.